The Effect of Traffic Intensity in Social Networking with a Special Reference to Whats App: A Case Study - K. V. Ramesh Babu, D. Sravani, P. Bhargava Kumar, N. Venkateswarlu, B. Lingarao (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Now-a-days people are expressing their feelings or emotions like happiness, sadness, anxieties etc. with others, through social media. Most of the people in the world have been giving lot of importance to social media. People like to share their feelings through social media applications such as Facebook, twitter, Whats App etc. Social media plays a vital role in the present human being’s life scenario. People want to share their memorable events such as birthday, marriage, engagement, job, promotions etc. among all social media applications of which mostly used by the people is Whats App. In this research paper we have obtained The Effect of Traffic Intensity in Social Networking with a special reference to Whats App:A Case Study and the status of viewers’ data from a social media application and analysed the characteristics of queuing in social platform.